THE INFLUENCE OF WORK POLICIES AND WORK CONFLICT ON EMPLOYEE INTENTION - Wakil, Abdul (universitas Islam Zainul Hasan Genggong, 2024)
This study aims to determine the effect Worklife-Policies, Work Involvement, and Work-Family Conflict on Turnover Intention of employees at PT. Sinar Bodhi Cipta, Tanjungpinang. This type of research uses a quantitative descriptive method. The sample in this study consisted of 93 people, namely employees of PT. The sample technique used in this study was the distribution of proportion sampling. The data analysis method used consisted of testing the quality of the data (validity). and reliability) Test classic assumptions (normality, heteroscedasticity, multicolonierity, and autocorrelation) Hypothesis test (t test and f test), multiple linear regression test and coefficient of determination. The results can be concluded that the work-life policies, Job Involvement, and Workfamily Conflict variables partially or simultaneously have a positive and significant effect on employee turnover intention at PT Sinar Bodhi Cipta, Tanjungpinang with a contribution of R square of 73.1%